Building a Sustainable Crowdfunding Model: Application of Maqashid Shariah in Collecting Infaq, Alms and Waqf in the Digital Era - Nita, Anita; Akbar, Wahyu; Hanafi, Ahmad; Noor Sayuti, Muhammad (Universitas Islam Negeri Sunan Ampel Sunan Ampel, 2025)
the implementation of infaq, sedekah and waqf crowdfunding in the perspective of Maqāṣid sharia, especially in the digital era, has now experienced an increase in reach and transparency so that it becomes an innovative fundraising model in the context of Islam. The purpose of this study is to explore the relevance of Maqāsid sharia, especially in maintaining religion (ḥifẓ al-dīn), soul (ḥifẓ al-nafs), reason (ḥifẓ al-'aql), descendants (ḥifẓ al-nasl) and property (ḥifẓ al-māl) as a guideline in formulating a more effective, efficient, and equitable management model for infaq, sedekah and waqf crowdfunding and to explore more deeply the mafsadat and mudharat of maqashid sharia in infaq, sedekah and waqf crowdfunding. This study uses a library method by analyzing various relevant literature sources. The results of the study indicate that when crowdfunding infaq, sedekah and waqf is carried out in accordance with the principles of maqāṣid sharia, it can become an innovative and sustainable model in managing social funds. In addition, when there is misappropriation in the management process, it will trigger mafsadat and mudharat which will result in failure to realize the welfare of the community. The author's recommendation based on this study is to improve the system with a basis of transparency, regulation, and education based on maqāṣid sharia. In addition, solid collaboration between the government, platforms, and Islamic financial institutions is very necessary in order to encourage the realization of a sustainable ecosystem